Analisis risiko kecelakaan kerja pada proses pengantongan dan pergudangan dengan pendekatan House of Risk dan Fault Tree Analysis (Studi kasus: Perusahaan Pupuk di Indonesia) - Izhaq, Dhuha Cahya; Dewi, Sinta (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The bagging and warehousing process is a critical operational activity in the Bagging & Warehousing Department of PT ABC. This process is not exempt from occupational health and safety issues. The causes are divided into two categories: unsafe conditions, such as working at heights, and unsafe acts, such as improper use of personal protective equipment (PPE). This study aims to identify high-priority risks, determine root causes, and design mitigation strategies to minimize risks in Bagging and Warehousing IV at PT ABC. The methods used include the House of Risk to identify risks and prioritize mitigations and Fault Tree Analysis to determine the root causes of risks. The findings reveal 10 potential risk events triggered by 8 main sources, with four primary risks: risk agent A8 (ARP 1616), A7 (ARP 1068), A1 (ARP 639), and A4 (ARP 552). The study recommends improving PPE usage behavior and ensuring ergonomic working conditions for bagging and warehousing workers.